Evaluation of the clinical outcomes and patient satisfaction related to the use of internal eye shields for electron external beam radiation therapy - Kirsty Tait; Sinead Burgess; Elizabeth A. Burmeister; Thuan Anh Le Nguyen; Bryan Burmeister (Journal of Medical Radiation Sciences)
Abstract Introduction Cancers around the eye are often treated using orthovoltage machines or by plastic surgery, neither of which are widely available in regional Australia. External beam radiation therapy (EBRT) using electrons and an internal eye shield is an alternative, relatively underreported technique which can provide similar cosmetic and functional outcomes. This report aimed to describe the process for the use of internal eye shields at GenesisCare Fraser Coast Radiation Oncology (GCFCRO) and the associated clinical outcomes and patient perceptions of the delivery and results of this procedure. Methods This project was conducted in two phases. Phase I was an audit of the departmental technique and short‐term clinical outcomes of 17 patients who received EBRT for skin cancer near the eyes at GCFCRO in partnership with Wide Bay Hospital and Health Service (WBHHS). Phase II was a survey of nine of those patients to elicit the patient perspective of the delivery and long‐term outcomes of the treatment. Results Phase I revealed the departmental procedures for simulation, planning and treatment at GCFCRO are consistent with other departments published protocols. Phase II results detailed positive patient perspectives regarding cosmetic outcomes and receipt of EBRT for skin cancer near their eyes. Conclusion EBRT with an internal eye shield is an acceptable alternative modality to surgery for squamous cell carcinomas (SCC) and basal cell carcinomas (BCC) around the eye in the definitive and adjuvant setting. This is particularly important in regional locations to facilitate patients receiving high‐quality care and outcomes locally.